Cleavage of MALAT1 RNA by 14-nt sgRNA-guided tRNase ZL - Masayuki Takahashi; Masayuki Nashimoto (PLoS ONE, 2025)
We have been developing a gene suppression technology, tRNase Z L -utilizing efficacious (TRUE) gene silencing, in which artificially designed small guide RNA (sgRNA) guides tRNase Z L to cleave cellular target RNA. In this study, we examined 14-nt linear-type sgRNAs, which are fully 2′- O -methylated and have full phosphorothioate linkages, for their ability to suppress a level of a nuclear-localized long non-coding RNA, Metastasis Associated Lung Adenocarcinoma Transcript 1 (MALAT1). The MALAT1 RNA is implied to be involved in stress responses and diseases including cancers. Specifically, we designed six 14-nt linear-type sgRNAs, sgRM1 − sgRM6 that target the human MALAT1 RNA. sgRM1, sgRM2 and sgRM6 suppressed the MALAT1 RNA level, while the other sgRNAs showed little effect. In order to demonstrate that the suppression effect of sgRM1, sgRM2 and sgRM6 on the MALAT1 RNA level is caused by TRUE gene silencing, we performed in vitro tRNase Z L cleavage assay, microscopic analysis for nuclear existence of sgRNA, and tRNase Z L knockdown experiment. For the in vitro tRNase Z L cleavage assay, three 30-nt MALAT1 RNA fragments, TM1, TM2 and TM6 were prepared, which were RNA targets for sgRM1, sgRM2 and sgRM6, respectively. All of the sgRNAs guided recombinant tRNase Z L in vitro to cleave their own targets, although the cleavage efficiency changed depending on target/sgRNA pairs. By fluorescence microscopy, a 14-nt 5′-Alexa568-labeled sgRNA released from liposome was observed to be distributed ubiquitously in A549 cells with higher density in the nucleus, where both the target MALAT1 RNA and tRNase Z L exist. Knockdown of tRNase Z L by siRNA attenuated the suppression effect of sgRM1, sgRM2 and sgRM6 on the MALAT1 RNA level. We also demonstrated that the effective sgRNAs sgRM1, sgRM2 and sgRM6 reduce A549 cell viability.